2000
DOI: 10.1002/(sici)1099-0461(2000)14:4<204::aid-jbt4>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CYP1A by carbofuran in primary culture of fish hepatocytes

Abstract: Carbofuran is a nematicide used in agricultural fields throughout the world. Indiscriminate use of this pesticide poses severe detrimental effects on our ecosystem. We have shown that it induces the CYP1A (cytochrome P4501A) monooxygenase enzyme system in cultured hepatocytes from Indian catfish, Heteropneustes fossilis (Bloch). We have quantified this induction by measuring the activity of the enzyme 7‐ethoxyresorufin‐O‐deethylase (EROD), synthesized from CYP1A1 gene. The induction followed a dose‐dependent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The potential use of lysozyme as an anticancer drug and in the treatment of HIV infection has also been discussed [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The potential use of lysozyme as an anticancer drug and in the treatment of HIV infection has also been discussed [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Isolation of hepatocytes from catfish liver and their culture were done following the methods routinely used in our laboratory [11].…”
Section: Culture Of Catfish Hepatocytesmentioning
confidence: 99%
“…Our laboratory reported that cytochrome P4501a might be involved in degradation of this pesticide in hepatocytes [11,12,13]. The mechanism of degradation is also associated with the induction of several critical pathways including, PI3 kinase, PKC, and HSP70 [12].…”
Section: Introductionmentioning
confidence: 97%
“…Isolation of hepatocytes from catfish liver and their culture were done following the methods routinely used in our laboratory (Ghosh et al 2000).…”
Section: Culture Of Catfish Hepatocytesmentioning
confidence: 99%
“…The procedure of EROD activity assay was followed as described before (Ghosh et al 2000). Table 1 Composition and amount of reagents used to assay the PKC.…”
Section: Assay Of Ethoxyresorufin-o-deethylase Activity (Erod) Activitymentioning
confidence: 99%